İŞ HUKUKUNDA ÜCRETSİZ İZİN UYGULAMALARI - (:unkn) unknown (My University, 2014)
Ücretsiz izin uygulaması iş sözleşmesinin askıya alınmasına ilişkin özel bir uygulamadır. Özellikle ekonomik kriz dönemlerinde işverenler, işçileri ücretsiz izne çıkararak, ekonomik konjonktürün işletme üzerindeki olumsuz etkilerini hafifletmeyi amaçlamaktadırlar. Ücretsiz izinle ilgili İş Kanununda herhangi bir düzenleme bulunmamaktadır. Ancak, bazı hükümlerde ücretsiz izin niteliğinde düzenlemelerin yer aldığı görülmektedir. Uygulamada işverenlerin, çoğu kez, tek taraflı olarak işçileri ücretsiz izne çıkarttığına rastlanmaktadır. Bu bağlamda karşılaşılan sorunların çözümü bakımından ücretsiz izin uygulamasının kanunla düzenlenmesinin bir gereksinim olduğu söylenebilir.

Leave without pay application is a specialized application for suspension of implementation of the employment contract. Especially during economic crisis periods, the employers, with the aim to mitigate the negative effects of the economic conjuncture on enterprises, apply leave without pay procedure for the employees. There is not any provision existed in Turkish Labour Law related to leave without pay. However, it is possible to find some provisions in the Code which is appropriate with the nature of unpaid leave. In practice the employers usually lets the employees go on unpaid leave unilaterally. In this context, to find a solution to the problems faced related to the application of the unpaid leave, it is needed to regulate this concept in Labour Law specifically.
Leave Without Pay App lications in Labour Law
Keywords: İktisat